Sale and Purchase of Rights to State Land Which is a Public Facility in a Residential Area - Walujo, Christianto Rici; Borman, M. Syahrul; Sidarta, Dudik Djaja; Handayati, Nur (Institute for Law and Economics Studies, 2025)
This study looks at how the law is applied to regulations pertaining to the supply of social and public services in Makassar City settlements, as well as the status of land ownership certificates for public facilities located above communities. The normative-empirical legal research used in this study was gathered from relevant literature and field research. Questionnaires and primary data are the types of data that are used. The legislation also comprises basic prin-ciples and requirements, rights to land, water and space as well as land registration, penal and transitional regulations. The findings indicate that Makassar City Regional Regulation Number 9 of 2011 concerning Provision and Delivery of Infrastructure, Facilities, Utilities in Industrial, Trade, Housing, and Settlement Areas, specifically funds in general, contains the regulations pertaining to the process for the delivery of public and social facilities in Makassar City settlements. outlined in Minister of Home Affairs Regulation Number 9 of 2009, which relates to Guidelines for the Provision of Facilities, Utilities, and Housing and Settlement Infrastructure in the Regions. In accordance with the law, the question of the certificate of property rights over public and social facilities must be fairly settled